2018
DOI: 10.1088/1367-2630/aaada0
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on THz yield from laser-produced solid density plasmas at relativistic laser intensities

Abstract: We experimentally characterize the generation of high-power terahertz radiation (THz) at the rear surface of a target irradiated by multiple laser pulses. A detailed dependence of the THz yield as a function of laser pulse duration, energy, target material and thickness is presented. We studied the THz radiation emitted mainly in two directions from the target rear surface, namely target normal (acceptance angle 0.87 sr) and non-collinear direction (perpendicular to the target normal directionacceptance angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 51 publications
(71 reference statements)
5
51
0
Order By: Relevance
“…This agrees well with the behavior expected from the plasma expansion model, which phenomenologically describes the THz generation mechanism under intense laser-solid interaction [24]. It says that THz radiation is emitted by the charge particle acceleration process at the foil rear surface, and the polarization of the radiation is radial.…”
Section: Lettersupporting
confidence: 87%
See 3 more Smart Citations
“…This agrees well with the behavior expected from the plasma expansion model, which phenomenologically describes the THz generation mechanism under intense laser-solid interaction [24]. It says that THz radiation is emitted by the charge particle acceleration process at the foil rear surface, and the polarization of the radiation is radial.…”
Section: Lettersupporting
confidence: 87%
“…Further analysis also reveals that the detected THz pulse exhibits quasi-single-cycle waveform with temporal durations of approximately 220 fs and 600 fs for transverse (ε y ) and longitudinal (ε z ) polarizations, respectively. This difference in the detected temporal structure of the waveforms can be ascribed to the difference in the response function of the two crystals used here [24,28], clearly supported by the respective THz spectra shown in the inset of Fig. 3(a).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Very recently, multimillijoule THz pulses have been demonstrated experimentally [31]. For the THz emissions from the rear side of a solid target [31][32][33][34][35][36][37][38][39][40], a number of studies have been reported on the influence of laser and target parameters on the THz radiation, and several distinct models have been proposed to understand the specific experimental observations. Nevertheless, the distinctions of these models and their respective contributions to the global THz radiation remain elusive, even under comparable laser conditions [32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%